Trends and Variations in Perinatal Mortality and Low Birthweight: The Contribution of Socio-economic Factors - Luginaah, Isaac N. (Can J Public Health, 1999)
Objective: To examine trends and regional variations in perinatal mortality and low birthweight (LBW) and regional variations in socioeconomic risk factors. Methods: Population-based study of Central West Region of Ontario with approximately 28,000 births annually during the period 1988–1995 using vital statistics records and Census data. Results and Conclusions: There was no significant change in the perinatal mortality rate averaging 9.4 per 1,000 births per year. The LBW rate increased from 49.7 to 54.8 per 1,000, while the prematurity rate increased from 56.1 to 75.8 per 1,000. Significant variation occurred in outcomes among different regions, which was partially explained by socio-economic factors. The increases in LBW and prematurity rate emphasize the need for effective targeted services and programs. In their planning and implementation, regional variations in socio-economic factors, and other factors such as: the availability and utilization of services and barriers to access in services, require further evaluation and consideration.